(untitled) (Development Service Industry Management, 2023)
The article presents the classification of leisure events. The modern leisure industry has developed intensively in quantity and quality over the past two decades and almost until 2020. The emergence and spread of the covid pandemic and the full-scale invasion of the Russian Federation significantly slowed down this process. The analysis shows that in the mentioned period the demand for event management in the field of leisure increased significantly. During this period, in the cultural space of the country, numerous types of events gained wide distribution and interest among many strata of the population. At the same time, it should be noted that at present, a single typology of events as leisure activities has not been formed in the scientific literature. This is explained by the fact that leisure is a multi-vector field in terms of directions, large-scale in scope and diverse in content. The article forms a classification of events based on such features as the content and nature of such events. The description of the main types in the typology of events in the field of leisure is also given. The proposed typology can enable business entities (event campaigns or event agencies) to more effectively choose certain types of events, based on the purpose, goals and tasks of the events, available resources and existing restrictions.